Phenolic compounds in Chinese purple yam and changes during vacuum frying - Fang, Zhongxiang; Wu, D.; Yü, D.; Ye, X.; Liu, D.; Chen, J. (2011)
Phenolic compounds and their changes during vacuum frying were investigated for a Chinese purple yam. Three cyanidin derivatives and one peonidin derivative were tentatively identified by HPLC-DAD-ESIMS analysis; sinapic acid and ferulic acid were identified by HPLC-DAD analysis with authentic chemicals. There were 31.0 mg/100 g (dry weight, DW) of total anthocyanin (ACN) and 478 mg/100 g DW of total phenolic content (TPC) in the fresh yam. Sinapic acid and ferulic acid were 135 and 31.3 mg/100 g DW respectively. The blanching process caused about 60% of ACN, and 30-50% of phenolic acids and TPC to be lost, which showed that anthocyanins were most vulnerable during blanching. The retention rate of the phenolic compounds during vacuum frying was 60-69%, indicating it was a practical technology for purple yam processing, on account of its impact on the phenolic compounds stability. © 2011 Elsevier Ltd. All rights reserved.